Discourse strategies and ideology in selected radio lead news of osun state broadcasting corporation, Nigeria - Alo, Moses; Ajewole-Orimogunje, Christiana Oluremi (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This study investigates discourse strategies and ideology employed in selected radio lead news of Osun State Broadcasting Corporation (OSBC), Osogbo, Nigeria. The analysis is done within the framework of critical discourse analysis which uncovers implicit ideology and exposes ideological bias and the exercise of power in text; and Halliday’s systemic functional grammar which emphasises the form/function relationship of language use in context. The data cover selected radio lead news purposively sampled based on the content from the period of January 2006 to December 2008.The analysis shows that journalists employ a variety of strategies to influence the way people understand issues or situations for the purpose of changing their actions and expectations in ways that are desirable to the political actors. The analysis reveals that media messages contain a lot of discourse strategies such as blame transfer, source avoidance, positive-self presentation and negative-other presentation, authoritarianism as a source of news making, foregrounding and informativeness, use of figures and statistics and metaphorisation. This study reveals that broadcast news contains hidden and subjective meanings displayed by a variety of strategies that highlight pro-government activities. It reveals that critical discourse analysis is relevant in interpreting and analyzing news discourse to discover hidden meanings, elicit meaning from news reports and to uncover ideological assumptions that are embedded in news texts.